Microphytobenthos as a source of labile organic matter for denitrifying microbes. (30th September 2022) - Morelle, Jérôme; Roose-Amsaleg, Céline; Laverman, Anniet M.
Abstract: Nitrogen loads in natural waters remain elevated in populated and agricultural areas with serious impact on estuarine and coastal ecosystems. Intertidal sediments can play a significant role in attenuating the high nitrogen levels in water via microbial nitrate reduction, in general dominated by denitrification. These heterotrophic processes are heavily mediated by both the quantity and quality of organic matter available. Benthic microalgae were experimentally investigated as organic carbon source for denitrifying microbes in intertidal mudflat sediments from the Seine Estuary (France). Dry microphytobenthos (including algae and their extracellular polymeric substances) were added to sediments and nitrate reduction rates were monitored over a two-week period using anoxic controlled flow-through reactor approach. Our results show that microphytobenthos addition resulted in significantly higher nitrate reduction (67–332% increase), highly related to the added amount of microphytobenthos. Moreover, increase of the low molecular weight carbohydrates consumption (11–39%) highlight the measurable contribution of extracellular polymeric substances to the carbon consumption during nitrate reduction. The addition of microphytobenthos increased the abundance of nitrite reductase genes, especially those encoding the nirS gene (43–152% increase) while nitrous oxide reductase genes ( nosZ gene) remained constant. Microphytobenthos appeared to favor complete denitrification as suggested by an increase in nirS and a decrease in clade II nosZ gene copy numbers. This study confirms experimentally the assumption that microbes use microalgae and particularly labile extracellular polymeric substances as a carbon substrate for nitrate reduction. These results reinforce the impact played by microphytobenthos in intertidal mudflats by highlighting their role on denitrifying microbes and nitrate removal from water. Graphical abstract: Image 1 Highlights: MPB significantly increases nitrate reduction. MPB increases the abundance of nitrite reductase genes especially nirS . EPS contribute measurably to the carbon consumption during denitrification. Low molecular weight carbohydrates are the principal form of EPS used.